Battery electrode
By using binders of electroactive materials, conductive materials and lithiated maleic anhydride copolymers in the cathode of lithium-ion electrochemical cell, the problem of insufficient cathode capacity and Coulomb efficiency in the prior art is solved, and higher energy and power density is achieved.
Patent Information
- Application Number
- CN202311523696.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-08-25
- Filing Date
- 2023-11-15
- Publication Date
- 2025-02-25
AI Technical Summary
The cathodes of existing lithium-ion electrochemical cell units have insufficient capacity and Coulomb efficiency, making it difficult to meet products with high energy and/or high power requirements.
The electrodes are adopted that include an electroactive material, a conductive material and a binder of lithiated maleic anhydride copolymer, and the electrode capacity and Coulomb efficiency are improved by adjusting the proportion and structure of the material.
The improved capacity and Coulomb efficiency of the electrochemical cell are achieved, and the expansion of silicon particles can be handled more effectively, with good chemical resistance and heat resistance.
Smart Images

Figure CN119517932A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to electrodes (eg, sulfur-containing electrodes) for lithium-ion electrochemical cells and methods of forming the same. Background Art
[0002] Advanced energy storage devices and systems are needed to meet the energy and / or power requirements of a variety of products, including automotive products such as start-stop systems (e.g., 12 volt (V) start-stop systems), battery auxiliary systems, hybrid electric vehicles ("HEV"), and electric vehicles ("EV"). Typical lithium-ion batteries and lithium-sulfur batteries include at least two electrodes and an electrolyte and / or a separator. One of the two electrodes serves as a positive electrode or cathode and the other electrode serves as a negative electrode or anode. Each electrode is connected to a current collector (typically a metal, such as copper for the anode and aluminum for the cathode). A separator and / or electrolyte may be disposed between the negative electrode and the positive electrode. The electrolyte is suitable for conducting lithium ions between the electrodes and, like the two electrodes, may be in solid and / or liquid form and / or a mixture thereof in various cases. In the case of a solid-state battery comprising solid electrodes and a solid electrolyte, the solid electrolyte may physically separate the electrodes so that different separators are not required.
[0003] Lithium-sulfur batteries may include a cathode having a sulfur-based electroactive material such as elemental sulfur (S) and / or Li2Sx, where 1≤x≤8. Such cathodes typically include one or more electroactive material layers, including, for example, a plurality of electroactive material particles, disposed on or near one or more surfaces of a current collector.
[0004] It would be desirable to develop cathodes with improved capacity and coulombic efficiency, and methods of making the same, for electrochemical cells that can address these challenges, e.g., methods and materials that can be easily integrated into common manufacturing processes. Summary of the invention
[0005] In one exemplary embodiment, the present disclosure provides an electrode for an electrochemical cell. The electrode may include an electroactive material; a conductive material; and a binder comprising a lithiated maleic anhydride copolymer.
[0006] In addition to one or more features described herein, the electrode can include, based on the total weight of the electrode: 70 to 98 weight percent electroactive material; 1 to 20 weight percent conductive material; and 1 to 20 weight percent binder.
[0007] In another exemplary embodiment, the electroactive material may include sulfur.
[0008] In yet another exemplary embodiment, the electroactive material may include S, S8, Li2S8, Li2S6, Li2S4, Li2S2, Li2S, or combinations thereof.
[0009] In yet another exemplary embodiment, the conductive material may include carbon black, graphite, acetylene black, carbon nanotubes, carbon fibers, carbon nanofibers, graphene, graphene nanosheets, graphene oxide, nitrogen-doped carbon, metal powder, liquid metal, conductive polymers, or combinations thereof.
[0010] In yet another exemplary embodiment, the lithiated maleic anhydride copolymer may be formed by lithiating a maleic anhydride copolymer represented by Formula I:
[0011]
[0012] wherein R is alkyl, ether, sulfate, amide, ester or nitrate.
[0013] In yet another exemplary embodiment, the lithiated maleic anhydride copolymer may include poly(methyl vinyl ether-alt-lithium malate).
[0014] In one exemplary embodiment, the present disclosure provides an electrochemical cell for cycling lithium ions. The electrochemical cell may include a first electrode including a first electroactive material, a conductive material, and a binder including a lithiated maleic anhydride copolymer; a second electrode including a second electroactive material; and an electrolyte material.
[0015] In addition to one or more features described herein, the first electrode can include, based on the total weight of the first electrode: 70 to 98 weight percent first electroactive material; 1 to 20 weight percent conductive material; and 1 to 20 weight percent binder.
[0016] In another exemplary embodiment, the first electroactive material may include sulfur.
[0017] In yet another exemplary embodiment, the conductive material may include carbon black, graphite, acetylene black, carbon nanotubes, carbon fibers, carbon nanofibers, graphene, graphene nanosheets, graphene oxide, nitrogen-doped carbon, metal powder, liquid metal, conductive polymers, or combinations thereof.
[0018] In yet another exemplary embodiment, the lithiated maleic anhydride copolymer may be formed by lithiating a maleic anhydride copolymer represented by Formula I:
[0019]
[0020] wherein R is alkyl, ether, sulfate, amide, ester or nitrate.
[0021] In yet another exemplary embodiment, the lithiated maleic anhydride copolymer may include poly(methyl vinyl ether-alt-lithium malate).
[0022] In yet another exemplary embodiment, the second electroactive material may include lithium.
[0023] In yet another exemplary embodiment, the electrolyte material may include a lithium salt dissolved in an organic solvent.
[0024] In yet another exemplary embodiment, the lithium salt may include lithium hexafluorophosphate, lithium perchlorate, lithium tetrachloroaluminate, lithium iodide, lithium bromide, lithium thiocyanate, lithium tetrafluoroborate, lithium difluorooxalatoborate, lithium tetraphenylborate, lithium bis(oxalate)borate, lithium tetrafluorooxalatophosphate, lithium nitrate, lithium hexafluoroarsenate, lithium trifluoromethanesulfonate, lithium bis(trifluoromethanesulfonyl imide), lithium fluorosulfonyl imide, lithium fluoroalkyl phosphate, or a combination thereof; and the organic solvent may include cyclic carbonates, linear carbonates, aliphatic carboxylates, γ-lactones, chain structure ethers, cyclic ethers, sulfur compounds, or a combination thereof.
[0025] In one exemplary embodiment, the present disclosure provides a method for forming an electrode binder. The method may include obtaining a maleic anhydride copolymer; and lithiating the maleic anhydride copolymer to form an electrode binder.
[0026] In addition to one or more of the features described herein, the maleic anhydride copolymer can be represented by Formula I:
[0027]
[0028] wherein R is alkyl, ether, sulfate, amide, ester or nitrate.
[0029] In yet another exemplary embodiment, the maleic anhydride copolymer may include poly(methyl vinyl ether-alt-maleic anhydride).
[0030] The above features and advantages and other features and advantages of the present disclosure are apparent from the following detailed description when taken in conjunction with the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Other features, advantages and details appear, by way of example only, in the following detailed description, which refers to the accompanying drawings, in which:
[0032] Figure 1 schematically illustrates an exploded isometric view of a prismatic battery cell according to the present disclosure, the prismatic battery cell including an anode, an electrolyte material, a separator, and a cathode;
[0033] Figure 2 schematically illustrates a cross-sectional side view of an embodiment of a cathode;
[0034] Figure 3 Elements of a process for forming a cathode of a battery cell are schematically shown;
[0035] Figure 4 is a graphical illustration showing the electrochemical performance of Example 1;
[0036] Figure 5 is a graphical illustration showing the electrochemical performance of Comparative Example 1;
[0037] Figure 6 is a graphical illustration showing the electrochemical performance of Example 1; and
[0038] Figure 7 is a graphical illustration showing the electrochemical performance of Comparative Example 1. DETAILED DESCRIPTION
[0039] The following description is merely exemplary in nature and is not intended to limit the present disclosure, its application, or uses. It should be understood that throughout the drawings, corresponding reference numerals indicate the same or corresponding parts and features.
[0040] According to exemplary embodiments, electrodes for batteries (e.g., lithium-sulfur batteries) and methods of forming and using the same are disclosed. Such batteries can be incorporated into energy storage devices, such as rechargeable lithium-ion batteries, which can be used in automotive transportation applications (e.g., motorcycles, boats, tractors, buses, mobile homes, campers, and tanks). However, as non-limiting examples, the present technology can also be used in other electrochemical devices, including aerospace parts, consumer products, devices, buildings (e.g., houses, offices, sheds, and warehouses), office equipment and furniture, and industrial equipment machinery, agricultural or farm equipment, or heavy machinery. The present disclosure provides a rechargeable lithium-ion battery that exhibits improved capacity and coulombic efficiency.
[0041] Referring to the drawings, wherein like reference numerals correspond to the same or similar parts throughout the several views, Figure 1 An embodiment of a prismatic lithium-ion battery cell 10 is schematically shown, which includes an electrode pair 15 having a cathode 20, a separator 40, and an anode 30, which are arranged in a stack and sealed in a flexible bag 60 containing an electrolyte material 62. In one embodiment of the battery cell, a reference electrode can be arranged between the anode and the cathode. A first positive battery cell tab 26 and a second negative battery cell tab 36 protrude from the flexible bag 60. The terms "anode" and "negative electrode" are used interchangeably. The terms "cathode" and "positive electrode" are used interchangeably. A single electrode pair 15 including an arrangement of a cathode 20, a separator 40, and an anode 30 is shown. It should be understood that multiple electrode pairs 15 can be arranged and electrically connected in the flexible bag 60 depending on the application of the battery cell 10.
[0042] Cathode 20 includes a first electroactive material 22 disposed on a cathode current collector 24 , and cathode current collector 24 may have a foil portion 25 extending from the first electroactive material 22 to form a second cell tab 26 .
[0043] Anode 30 includes a second electroactive material 32 disposed on an anode current collector 34. Anode current collector 34 may be a metal substrate having a foil portion 35 extending from second electroactive material 32 to form a first cell tab 36.
[0044] Cathode current collector 24 and anode current collector 34 may be metal plate-shaped elements that contact the respective first electroactive material 22 and second electroactive material 32 over a considerable interfacial surface area. The purpose of cathode current collector 24 and anode current collector 34 is to exchange free electrons with the respective first electroactive material 22 and second electroactive material 32 during discharge and charge.
[0045] Cathode current collector 24 may be a metal substrate in the form of a planar sheet made of aluminum or an aluminum alloy and may have a thickness of, for example, 0.02 millimeters (mm). Separator 40 is disposed between cathode 20 and anode 30 to physically and electrically separate anode 30 from cathode 20.
[0046] Anode current collector 34 may be a flat plate-like metal substrate in the form of a rectangular planar sheet in an embodiment. In an embodiment, anode current collector 34 may be arranged as a planar sheet having a non-rectangular shape, a coiled configuration, a cylindrical configuration, or another configuration.
[0047] Anode current collector 34 may be made of one of copper, copper alloy, stainless steel, nickel, etc., or another material that does not alloy with lithium. In one embodiment, anode current collector 34 may have a thickness of, for example, 0.02 mm. Second electroactive material 32 is present in a second electroactive material layer, which may be applied to one or both surfaces of anode current collector 34.
[0048] The cathode current collector 24, the anode current collector 34, or a combination thereof may include stainless steel, aluminum, nickel, iron, titanium, copper, tin, a suitable conductive material, or a combination thereof. The cathode current collector 24, the anode current collector 34, or a combination thereof may be a coated foil, for example, wherein one side (e.g., the first side or the second side) of the current collector 24, 34 includes a metal (e.g., a first metal) and the other side (e.g., the other side of the first side or the second side) of the current collector 24, 34 includes another metal (e.g., a second metal). The coated foil may include, for example, aluminum copper (Al-Cu), nickel copper (Ni-Cu), stainless steel-copper (SS-Cu), aluminum-nickel (Al-Ni), aluminum-stainless steel (Al-SS), and nickel-stainless steel (Ni-SS). The cathode current collector 24, the anode current collector 34, or a combination thereof may be pre-coated, such as a graphene or carbon-coated aluminum current collector. The cathode current collector 24, the anode current collector 34, or a combination thereof may be in the form of a foil, a slit mesh, a woven mesh, or a combination thereof.
[0049] An electrolyte material 62 that conducts lithium ions may be contained within separator 40 and may be exposed to each of cathode 20 and anode 30 to allow lithium ions to move between cathode 20 and anode 30. Lithium ions may be stripped from anode 30 during discharge, or stripped from cathode 20 during charge, giving up electrons that flow through current collectors 34 and 24, respectively, through an external circuit connected to a load or charger, and then to the opposing current collectors (24 and 34) and electrodes (20 and 30), where they reduce lithium ions as they are intercalated.
[0050] The cathode 20 and the anode 30 are each manufactured as an electrode material capable of depositing and stripping lithium ions (on the anode) or inserting and deinserting (on the cathode). The electrode materials of the cathode 20 and the anode 30 are configured to store lithium at different electrochemical potentials relative to a common reference electrode (e.g., lithium). In the configuration of the electrode pair 15, the anode 30 stores deposited or plated lithium at a lower electrochemical potential (i.e., a higher energy state) than the cathode 20, so that when the anode 30 is lithiated, there is an electrochemical potential difference between the cathode 20 and the anode 30. The electrochemical potential difference of each battery cell 10 can result in a charging voltage in the range of 3V to 5V and a nominal open circuit voltage in the range of 2.9V to 4.2V, which can allow lithium ions to be reversibly transferred between the cathode 20 and the anode 30 spontaneously (discharge phase) or by applying an external voltage (charge phase) during the operating cycle. In one embodiment, the thickness of the anode 30 is 10μm to 20μm.
[0051] The first electroactive material layer 23 of the cathode 20 ( Figure 2) includes a first electroactive material 22, a first conductive material 28, and a lithiated maleic anhydride copolymer binder 29. Based on the total weight of the cathode, the cathode may include 30 wt% to 98 wt% of the first electroactive material, greater than 0 wt% to 30 wt% of the first conductive material, greater than 0 wt% to 20 wt% of the lithiated maleic anhydride copolymer binder, and 0 wt% to 30 wt% of the electrolyte material.
[0052] The cathode may be in the form of a layer having a thickness of 1 μm to 1,000 μm, for example 5 μm to 400 μm or 10 μm to 300 μm. The cathode may be defined by a plurality of first electroactive materials, for example, including the first electroactive material. The first electroactive material may have an average particle diameter of 0.01 μm to 50 μm, for example 1 μm to 20 μm.
[0053] The first electroactive material may be an electroactive material comprising sulfur, such as S, S8, Li2S8, Li2S6, Li2S4, Li2S2, Li2S, or a combination thereof. The electroactive material comprising sulfur should fully undergo lithiation and delithiation while serving as a positive terminal of a battery cell.
[0054] The first electroactive material can be present in the cathode in an amount greater than or equal to 50 wt%, greater than or equal to 60 wt%, greater than or equal to 70 wt%, greater than or equal to 80 wt%, greater than or equal to 90 wt%, greater than or equal to 95 wt%; or 50 wt% to 99 wt%, 70 wt% to 99 wt%, or 90 wt% to 99 wt%, based on the total weight of the cathode.
[0055] Cathode 20 may include a first conductive material 28. For example, first electroactive material 22 may be mixed with first conductive material 28 that provides an electron conduction path. First conductive material 28 may be present in cathode 20 in an amount of 1 to 20 wt%, 1 to 15 wt%, or 1 to 10 wt%, based on the total weight of cathode 20.
[0056] Examples of the first conductive material 28 include, for example, carbon black (such as Super P), graphite, acetylene black (such as KETCHEN TM Black or DENKA TM Black), carbon nanotubes, carbon fibers, carbon nanofibers, graphene, graphene nanosheets, graphene oxide, nitrogen-doped carbon, metal powders (e.g., copper, nickel, steel, or iron), liquid metals (e.g., Ga, GaInSn), conductive polymers (e.g., including polyaniline, polythiophene, polyacetylene, polypyrrole, etc.), or combinations thereof. As used herein, the term "graphene nanosheet" refers to a nanoplate or stack of graphene layers. This first conductive material 28 in the form of particles may have a circular geometry or an axial geometry.
[0057] The term "axial geometry" refers to particles that generally have a rod-like, fiber-like, or other cylindrical shape, which has a distinct long or elongated axis. The aspect ratio (AR) of a cylindrical shape (e.g., a fiber or rod) can be defined as AR=L / D, where L is the length of the longest axis and D is the diameter of the cylinder or fiber. Exemplary axial geometry electroactive material particles suitable for use in the present disclosure may have a high aspect ratio, for example, from 10 to 5,000. The first electroactive material particles having an axial geometry include fibers, wires, flakes, whiskers, filaments, tubes, rods, and the like. The term "circular geometry" is generally applicable to particles with a lower aspect ratio, for example, an aspect ratio closer to 1 (e.g., less than 10). It should be noted that the particle geometry may be different from a true circular shape, and may, for example, include an elliptical or oval shape, including a long oblate spheroid or an oblate spheroid, an agglomerated particle, a polygonal (e.g., a hexagonal) particle, or other shapes that generally have a low aspect ratio. An oblate spheroid may have a disk shape, which has a relatively high aspect ratio. Thus, particles of generally circular geometry are not limited to relatively low aspect ratio and spherical shapes.
[0058] The cathode 20 includes a lithiated maleic anhydride copolymer binder 29, for example, to structurally reinforce the first electroactive material 22. For example, the first electroactive material 22 can be mixed with the lithiated maleic anhydride copolymer binder 29 to improve the structural integrity of the cathode 20. The lithiated maleic anhydride copolymer binder 29 can be present in the cathode 20 in an amount of 1 wt % to 20 wt %, 1 wt % to 15 wt %, or 1 wt % to 10 wt %, based on the total weight of the cathode 20.
[0059] In one embodiment, the lithiated maleic anhydride copolymer binder may exhibit less capacity fade, provide a more robust mechanical network and improved mechanical properties to more effectively handle silicon particle expansion, and have good chemical and thermal resistance.
[0060] Examples of suitable maleic anhydride copolymers that can be lithiated to provide the lithiated maleic anhydride copolymer binder 29 as described herein include, for example,
[0061]
[0062] wherein R is an alkyl, ether, sulfate, amide, ester, nitrate, or other moiety that does not react with anhydride moieties (e.g., anhydride moieties of maleic anhydride copolymers). For example, poly(methyl vinyl ether-alt-maleic anhydride) can be lithiated as follows to provide a lithiated maleic anhydride copolymer (e.g., poly(methyl vinyl ether-alt-lithium malate)):
[0063]
[0064] Without wishing to be bound by any theory, it is believed that lithiation (eg, lithiation of maleic anhydride) can increase lithium ion transport. Different side groups, such as ethers, can help improve ion transport and increase solution wettability and different swelling properties.
[0065] The method of lithiating the maleic anhydride copolymer may include dissolving the maleic anhydride copolymer in water, adding lithium hydroxide, and drying the resulting lithiated maleic anhydride copolymer. The lithiation may be performed at a temperature, for example, below 100°C or below 70°C.
[0066] Figure 2 An embodiment of a cathode 20 is schematically shown after drying the first electroactive material slurry, the cathode 20 including a cathode current collector 24 having a first electroactive material layer 23 thereon. In one embodiment and as shown, the first electroactive material layer 23 can be applied to one side of the cathode current collector 24. The first electroactive material layer 23 can be applied to both sides of the cathode current collector 24. The first electroactive material layer 23 includes 70 wt % to 98 wt % of the first electroactive material 22, 1 wt % to 20 wt % of the first conductive material 28, and 1 wt % to 20 wt % of the lithiated maleic anhydride copolymer binder 29, based on the total weight of the first electroactive material layer 23.
[0067] In an embodiment, the first electroactive material layer 23 may have a thickness between 4 μm and 12 μm. In an embodiment, the first electroactive material layer 23 may have a thickness between, for example, 35 μm and 150 μm.
[0068] The first electroactive material slurry includes a mixture of the first electroactive material 22, the first conductive material 28, the lithiated maleic anhydride copolymer binder 29 and a solvent. The first electroactive material 22 may have a maximum particle size of 10 μm and a minimum particle size of 100 nm, with a minimum purity of 99.0%.
[0069] The lithiated maleic anhydride copolymer binder 29 is used as a binding material to combine the first conductive material 28, the first electroactive material 22, and the cathode current collector 24. The lithiated maleic anhydride copolymer binder 29 may be in the form of a powder, a resin, or dissolved in a solvent.
[0070] The mixture of the first electroactive material 22, the first conductive material 28 and the lithiated maleic anhydride copolymer binder 29 forming the first electroactive material layer 23 is mixed using an organic solvent or water to form a first electroactive material slurry, such as Figure 3 As shown in step S301 of process 300. The first electroactive material slurry including the first electroactive material layer 23 may be applied (eg, cast) onto the cathode current collector 24, as shown in FIG. Figure 3 As shown in step S302 of the process 300 , and drying is performed to form a cathode.
[0071] The first electroactive material layer 23 can be applied to the cathode current collector 24 by gravure coating, slot die coating or dip coating in one embodiment. Slot die coating is a deposition technique in which a slurry of the first electroactive material 22 is delivered to the substrate of the cathode current collector 24 via a narrow slot positioned close to the surface. The main advantage of the slot die coating method is the simple relationship between the wet film coating thickness, the solution flow rate and the speed of the coated substrate relative to the head. In addition, slot die coating can achieve extremely uniform films over large areas. Slot die coating is one of many methods that can be used to deposit thin liquid films onto substrate surfaces. One of the main advantages of slot die coating is that it can be easily integrated into scale-up processes, including roll-to-roll coating and sheet-to-sheet deposition systems.
[0072] The first electroactive material slurry including the first electroactive material layer 23 may be applied to the cathode current collector 24 by immersing the cathode current collector 24 in a bath including the first electroactive material slurry in the embodiment.
[0073] The cathode current collector 24 on which the first electroactive material layer 23 is applied is dried to bond the first electroactive material layer 23 to the surface of the cathode current collector 24 to form the cathode 20. Figure 3 As shown in step S303 of process 300. The drying process may include subjecting the cathode current collector 24 with the applied first electroactive material layer 23 to a high temperature environment for a period of time to remove the solvent, which may include subjecting the cathode current collector 24 with the applied first electroactive material layer 23 to a calendaring process to improve the adhesion of the first electroactive material layer 23 on the surface of the cathode current collector 24. After the first electroactive material layer 23 is bonded to the surface of the cathode current collector 24, the cathode current collector 24 with the applied first electroactive material layer 23 is subjected to a temperature between 60°C and 150°C for a period of 1 to 60 minutes to dry and remove the solvent.
[0074] The electroactive material layer of the anode may include a second electroactive material, a second conductive material, and a second binder. Based on the total weight of the anode, the anode may include 30 wt % to 100 wt % of the second electroactive material, 0 wt % to 30 wt % of the second conductive material, 0 wt % to 20 wt % of the second binder, and 0 wt % to 30 wt % of the electrolyte material.
[0075] The anode may be in the form of a layer having a thickness of 1 μm to 1,000 μm, for example 5 μm to 400 μm or 10 μm to 300 μm. The anode may be defined by a plurality of second electroactive materials, for example, including the second electroactive material. The second electroactive material may have an average particle diameter of 0.01 μm to 50 μm, for example 1 μm to 20 μm.
[0076] The anode includes a second electroactive material as a lithium host material, which can be used as a negative terminal of a lithium ion battery. For example, the anode can include a lithium host material (e.g., a second electroactive material) that can be used as a negative terminal of a battery cell. The anode can be defined by a plurality of particles of the second electroactive material.
[0077] The anode may include a second electroactive material comprising lithium, such as lithium metal, a lithium alloy (e.g., a lithium silicon alloy, a lithium aluminum alloy, a lithium indium alloy, a lithium tin alloy, or a combination thereof), or a combination thereof. The anode may also include silicon, tin oxide, aluminum, indium, zinc, germanium, silicon oxide, titanium oxide, lithium titanate, iron sulfide (FeS), Li4Ti5O 12 Or a combination thereof, such as silicon mixed with graphite. The anode itself may be lithium metal. In one embodiment, the anode may include lithiated graphite.
[0078] The second electroactive material can be present in the anode in an amount of 70 to 100 wt%, 70 to 98 wt%, 70 to 95 wt%, 80 to 95 wt%, based on the total weight of the anode.
[0079] The anode may include a second conductive material. For example, the second electroactive material may be mixed with a second conductive material that provides an electronic conduction path. The second conductive material may be present in the anode in an amount of 0 wt % to 30 wt %, 1 wt % to 25 wt %, 1 wt % to 20 wt %, 1 wt % to 10 wt %, 3 wt % to 20 wt %, or 5 wt % to 15 wt %, based on the total weight of the anode.
[0080] The second conductive material may be the same as or different from the first conductive material and may include, for example, carbon black (eg, Super P), graphite, acetylene black (eg, KETCHEN TM Black or DENKA TM black), carbon nanotubes, carbon fibers, carbon nanofibers, graphene, graphene nanosheets, graphene oxide, nitrogen-doped carbon, metal powders (e.g., copper, nickel, steel, or iron), liquid metals (e.g., Ga, GaInSn), conductive polymers (e.g., including polyaniline, polythiophene, polyacetylene, polypyrrole, etc.), or combinations thereof.
[0081] Anode can include a second binding agent. For example, the second electroactive material can be mixed with a second binding agent that improves the structural integrity of anode. Based on the gross weight of anode, the second binding agent can be present in anode with an amount of 0 wt % to 30 wt %, 1 wt % to 25 wt %, 1 wt % to 20 wt %, 1 wt % to 10 wt %, 3 wt % to 20 wt % or 5 wt % to 15 wt %. The second binding agent can include, for example, PTFE, sodium carboxymethyl cellulose (CMC), styrene-butadiene rubber (SBR), poly (vinylidene fluoride) (PVDF), acrylonitrile-butadiene rubber (NBR), styrene ethylene butylene styrene copolymer (SEBS), styrene butadiene styrene copolymer (SBS), lithium polyacrylate (LiPAA), sodium polyacrylate (NaPAA), sodium alginate, lithium alginate, ethylene propylene diene monomer (EPDM) or a combination thereof.
[0082] The separator may have a thickness between 10 μm and 50 μm. The separator may include a porous polymer (e.g., a polyolefin) that provides thermal stability. Examples of polyolefins include polyethylene (PE) (and variations such as high-density polyethylene (HDPE), low-density polyethylene (LDPE), linear low-density polyethylene (LLDPE), and ultra-high molecular weight polyethylene (UHMWPE)), polypropylene (PP), and blends of PE and PP. The polymer may electrically insulate and physically separate the cathode and anode.
[0083] The separator may be a solid polymer electrolyte material including a polymer such as polyethylene oxide (PEO), polypropylene oxide (PPO), polyacrylonitrile (PAN), a solid electrolyte material (e.g., an oxide-based electrolyte material or a sulfide-based electrolyte material), or a gel polymer electrolyte material having a lithium salt or swollen with a lithium salt solution. During applicable discharge and charge cycles, the cathode and the anode reversibly exchange lithium ions through the separator.
[0084] The separator may include, for example, a microporous polymer separator including a polyolefin or polytetrafluoroethylene (PTFE). The polyolefin may be a homopolymer (derived from a single monomer component) or a heteropolymer (derived from more than one monomer component), which may be linear or branched. If the heteropolymer is derived from two monomer components, the polyolefin may present any copolymer chain arrangement, including those of block copolymers or random copolymers. Similarly, if the polyolefin is a heteropolymer derived from more than two monomer components, it may also be a block copolymer or a random copolymer. The polyolefin may be polyethylene (PE), polypropylene (PP), or a blend of PE and PP, or a multilayer structured porous membrane of PE, PP, or a combination thereof, such as a PP-PE double-layer structure or a PP-PE-PP three-layer structure. Commercially available polyolefin porous separator membranes include those available from Celgard LLC. 2500 (single-layer polypropylene separator) and 2325 (three-layer polypropylene / polyethylene / polypropylene separator).
[0085] When the separator is a microporous polymer separator, it can be a monolayer or multilayer laminate, which can be manufactured by a dry or wet process. For example, in some cases, a monolayer polyolefin can form the entire separator. The separator can be a fiber separator having a large number of holes extending between the opposing surfaces, and can have an average thickness of, for example, less than one millimeter. Multiple discrete layers of similar or different polyolefins can be assembled to form a microporous polymer separator. The separator can include polymers other than polyolefins, such as polyethylene terephthalate (PET), polyvinylidene fluoride (PVDF), polyamide, polyimide, poly (amide-imide) copolymer, polyetherimide, cellulose or a combination thereof, or any suitable material for producing a desired porous structure. The separator can include a cellulose separator, a PVDF separator and a porous polyimide separator.
[0086] The separator may include a high temperature stable polymer, such as a nonwoven based on polyimide nanofibers, a polyethylene separator coated with nano-sized Al2O3 and poly(4-styrene sulfonate lithium), a polyethylene coated with SiO2, a polyethylene coated with a copolyimide, polyetherimide (PEI), bisphenol acetone diphthalic anhydride (BPADA) and p-phenylenediamine, expanded polytetrafluoroethylene reinforced polyvinylidene fluoride-hexafluoropropylene, etc. The separator may be a high temperature stable separator and include a sandwich structured PVDF / poly(m-phenylene isophthalamide) (PMIA) / PVDF nanofiber separator.
[0087] The separator may include a ceramic coating, a heat-resistant material coating, or a combination thereof. The ceramic coating, the heat-resistant material coating, or a combination thereof may be disposed on one or more sides of the separator. The material forming the ceramic coating may be aluminum oxide (Al2O3), silicon dioxide (SiO2), titanium dioxide (TiO2), or a combination thereof. The heat-resistant material may be, for example, Nomex, aramid, or a combination thereof. A polymer (e.g., a polyolefin) may be included in the separator as a fiber layer to help provide the separator with appropriate structural and porosity characteristics.
[0088] The separator may be permeated with a liquid electrolyte material throughout the pores of the polymer. The liquid electrolyte material that wets both the cathode and the anode may include a lithium salt dissolved in a non-aqueous solvent. The liquid electrolyte material may wet the separator (e.g., fill 5% to 100%, such as 90%, of the porosity of the separator).
[0089] The cathode, anode, and separator may each include an electrolyte material, such as within its pores, capable of conducting lithium ions between the anode and cathode. Any suitable electrolyte material, whether in solid, liquid, or gel form, capable of conducting lithium ions between electrodes may be used in the battery cell. For example, the electrolyte material may be a non-aqueous liquid electrolyte solution comprising a lithium salt dissolved in an organic solvent or a mixture of organic solvents.
[0090] Suitable lithium salts may have an inert anion. Exemplary lithium salts that can be dissolved in an organic solvent or a mixture of organic solvents to form a non-aqueous liquid electrolyte solution include lithium hexafluorophosphate (LiPF6), lithium perchlorate (LiClO4), lithium tetrachloroaluminate (LiAlCl4), lithium iodide (LiI), lithium bromide (LiBr), lithium thiocyanate (LiSCN), lithium tetrafluoroborate (LiBF4), lithium difluorooxalatoborate (LiBF2(C2O4))(LiODF), lithium tetraphenylborate (LiB(C6H5)4), bis(oxalate) Lithium borate (LiB(C2O4)2) (LiBOB), lithium tetrafluorooxalophosphate (LiPF4(C2O4)) (LiFOP), lithium nitrate (LiNO3), lithium hexafluoroarsenate (LiAsF6) lithium trifluoromethanesulfonate (LiCF3SO3), lithium bis(trifluoromethanesulfonylimide) (LiTFSI) (LiN(CF3SO2)2), lithium fluorosulfonylimide (LiN(FSO2)2) (LiFSI), lithium fluoroalkyl phosphate (LiFAP) (Li3O4P) or a combination thereof.
[0091] The lithium salt may be dissolved in various organic solvents, including, for example, alkyl carbonates, such as cyclic carbonates (e.g., ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), fluoroethylene carbonate (FEC)), linear carbonates (e.g., dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC)), aliphatic carboxylates (e.g., methyl formate, methyl acetate, methyl propionate), γ-lactones (e.g., γ-butyrolactone, γ-valerolactone), chain structure ethers (e.g., 1,2-dimethoxyethane (DME), 1,2-diethoxyethane, ethoxymethoxyethane), cyclic ethers (e.g., tetrahydrofuran, 2-methyltetrahydrofuran, 1,3-dioxolane (DOL)), sulfur compounds (e.g., sulfolane), or combinations thereof. The electrolyte material may include 0.5 mol / L (mol (M)) to 4.0 M of one or more lithium salts. When the electrolyte material has a lithium concentration greater than 2 M or an ionic liquid, the electrolyte material may include a diluent such as fluoroethylene carbonate (FEC), hydrofluoroether (HFE), or a combination thereof.
[0092] An electrolyte material, such as a solid electrolyte, can be used as a conductor and separator for lithium ions, such that different separator components may not be present. The solid electrolyte particles can include oxide-based particles, sulfide-based particles, metal-doped or aliovalent-substituted oxide particles, inactive oxide particles, nitride-based particles, hydride-based particles, halide-based particles, borate-based particles, or combinations thereof.
[0093] The oxide-based particles can include garnet ceramics, LISICON-type oxides, NASICON-type oxides, perovskite-type ceramics, or combinations thereof. For example, the garnet ceramic can be Li7La3Zr2O 12 , Li 6.2 Ga 0.3 La 2.95 Rb 0.05 Zr2O 12 , Li 6.85 La 2.9 Ca 0.1 Zr 1.75 Nb 0.25 O 12 , Li 6.25 Al 0.25 La3Zr2O 12 , Li 6.75 La3Zr 1.75 Nb 0.25 O 12 or combinations thereof. The LISICON-type oxide can be Li 2+2x Zn 1-x GeO4 (where 0 < x < 1), Li 14 Zn(GeO4)4, Li 3+x (P 1-x Si x )O4 (where 0 < x < 1), Li 3+x Ge x V 1-x O4 (where 0 < x < 1) or combinations thereof. The NASICON-type oxide can be defined by LiMM′(PO4)3, where M and M′ are independently Al, Ge, Ti, Sn, Hf, Zr, or La. For example, the NASICON-type oxide can be Li 1+x Al x Ge 2-x (PO4)3 (LAGP) (where 0 ≤ x ≤ 2), Li 1.4 Al 0.4 Ti 1.6 (PO4)3, Li 1.3 Al 0.3 Ti 1.7(PO4)3, LiTi2(PO4)3, LiGeTi(PO4)3, LiGe2(PO4)3, LiHf2(PO4)3, or a combination thereof. The perovskite-type ceramic can be Li 3.3 La 0.53 TiO3, LiSr 1.65 Zr 1.3 Ta 1.7 O9, Li 2x-y Sr 1-x Ta y Zr 1-y O3 (where x = 0.75y and 0.60 < y < 0.75), Li 3 / 8 Sr 7 / 16 Nb 3 / 4Zr 1 / 4 O3, Li 3x La (2 / 3 - x) TiO3 (where 0 < x < 0.25), or a combination thereof.
[0094] The metal-doped or aliovalent-substituted oxide particles can include, for example, Al (aluminum)- or Nb (niobium)-doped Li7La3Zr2O 12 , Sb (antimony)-doped Li7La3Zr2O 12 , Ga (gallium)-doped Li7La3Zr2O 12 , Cr (chromium) and V (vanadium)-substituted LiSn2P3O 12 , Al (aluminum)-substituted Li 1+x+y Al x Ti 2-x Si Y P 3-y O 12 (where 0 < x < 2 and 0 < y ≤ 3), or a combination thereof.
[0095] The sulfide-based particles can include, for example, pseudo-binary sulfides, pseudo-tertiary sulfides, pseudo-quaternary sulfides, or a combination thereof. Exemplary pseudo-binary sulfide systems include the Li2S-P2S5 system (e.g., Li3PS4, Li7P3S 11 and Li 9.6 P3S 12 ), the Li2S-SnS2 system (e.g., Li4SnS4), the Li2S-SiS2 system, the Li2S-GeS2 system, the Li2S-B2S3 system, the Li2S-Ga2S3 system, the Li2S-P2S3 system, the Li2S-Al2S3 system, Li 3.4 Si 0.4 P 0.6 S4, Li 10 GeP2S 11.7 O0.3 , lithium silver mine Li6PS5X (wherein X is one of Cl, Br and I). Exemplary pseudo-ternary sulfide systems include Li2O-Li2S-P2S5 system, Li2S-P2S5-P2O5 system, Li2S-P2S5-GeS2 system (e.g., Li 3.25 Ge 0.25 P 0.75 S4 (sulfo-LISICON) and Li 10 GeP2S 12 (LGPS)), Li2S-P2S5-LiX system (wherein X is one of F, Cl, Br and I) (e.g., Li6PS5Br, Li6PS5Cl, L7P2S8I and Li4PS4I), Li2S-As2S5-SnS2 system (e.g., Li 3.833 Sn 0.833 As 0.166 S4), Li2S-P2S5-Al2S3 system, Li2S-LiX-SiS2 system (where X is one of F, Cl, Br and I), 0.4LiI·0.6Li4SnS4 and Li 11 Si2PS 12 Exemplary pseudo-quaternary sulfide systems include the Li2O-Li2S-P2S5-P2O5 system, Li 9.54 Si 1.74 P 1.44 S 11.7 C l0. 3. Li 9.6 P3S 12 、Li7P3S 11 、Li9P3S9O3、Li 10.35 Ge 1.35 P 1.65 S 12 , Li 10.35 Si 1.35 P 1.65 S 12 , Li 9.81 Sn 0.81 P 2.1.9 S 12 , Li 10 (Si 0.5 Ge 0.5 )P2S 12 , Li 10 (Ge 0.5 Sne 0.5 )P2S 12 , Li 10 (Si 0.5 Sn 0.5 )P2S 12 、Li7P2.9 Mn 0.1 S 10.7 I 0.3 , Li 3.833 Sn 0.833 As 0.166 S4, LiI-Li4SnS4, Li4SnS4 and Li 10.35 [Sn 0.27 Si 1.08 ]P 1.65 S 12 .
[0096] Inactive oxide particles may include, for example, SiO2, Al2O3, TiO2, ZrO2, or a combination thereof; nitride-based particles may include, for example, Li3N, Li7PN4, LiSi2N3, or a combination thereof; hydride-based particles may include, for example, LiBH4, LiBH4-LiX (wherein X=Cl, Br or I), LiNH2, Li2NH, LiBH4-LiNH2, Li3AlH6, or a combination thereof; halide-based particles may include, for example, LiI, Li3InCl6, Li2CdCl4, Li2MgCl4, LiCdl4, Li2ZnI4, Li3Ocl, Li3Ycl6, Li3Ybr6, or a combination thereof; and borate-based particles may include, for example, Li2B4O7, Li2O-B2O3-P2O5, or a combination thereof.
[0097] The descriptions set forth herein regarding cathode, anode, separator, and electrolyte materials are intended to be non-limiting examples. Many variations in the chemistry of each element may be employed in the context of the lithium-ion battery cells of the present disclosure.
[0098] Example
[0099] Button cells were fabricated with cathodes having XE2B (porous carbon host) and sulfur (at a ratio of 20 wt. % porous carbon to 80 wt. % encapsulated sulfur). The cathode had a carbon content of about 4.2 mg / cm2 (mg / cm 2 ) of sulfur as the electrochemically active material. The 13 millimeter (mm) diameter cathode had about 5.57 milligrams (mg) of sulfur. The total weight of the cathode material was about 8 mg of material - about 6.96 mg of carbon / sulfur composite, about 0.64 mg of multi-walled carbon nanotube conductive carbon, and about 0.4 mg of binder (87:8:5 weight ratio of carbon / sulfur composite: conductive carbon: binder).
[0100] The anode was a lithium metal chip. The battery included a 40 microliter (μL) amount of 1,3-dioxolane (DOL)-1,2-dimethoxyethane (DME) 0.6 mol / L (mol (M)) M lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) 0.4 M LiNO3 in a liquid electrolyte material and a Celgard polypropylene separator.
[0101] Figure 4 is a graph of the specific discharge capacity (milliampere-hour / gram (mAh / g)) (400), specific charge capacity (mAh / g) (410), and coulombic efficiency (percent (%)) (420) versus cycle number for Example 1 (poly(methyl vinyl ether-alt-malate) binder), and Figure 5 is a graph of the specific discharge capacity (mAh / g) (500), specific charge capacity (mAh / g) (510), and coulombic efficiency (%) (520) versus cycle number for Comparative Example 1 (carboxymethyl cellulose (CMC) binder). Figure 6 is a graph of voltage (volts (V)) versus specific capacity (mAh / g) for Example 1 (poly(methyl vinyl ether-alt-malate) binder), and Figure 7 is a graph of voltage (V) versus specific capacity (mAh / g) for Comparative Example 1 (CMC binder).
[0102] By comparison Figure 4 and Figure 5 and Figure 6 and Figure 7 As can be seen, the disclosed lithiated maleic anhydride copolymer binder exhibits greater capacity and coulombic efficiency over 100 cycles. See, for example, Example 1 exhibits a relatively lower level of charge separation compared to Comparative Example 1, which exhibits less energy loss. Figure 4 and Figure 5 The Coulombic efficiency shown demonstrates that Example 1 has greater stability over time than Comparative Example 1. Figure 6 and Figure 7 As shown, Example 1 thus has fewer side reactions than Comparative Example 1, where the extra current may be directed to undesired electrochemical processes contrary to the primary electrochemical properties of the battery cell.
[0103] The terms "a" and "an" do not indicate a limitation of quantity, but rather indicate the presence of at least one of the referenced item. Unless the context clearly indicates otherwise, the term "or" means "and / or". References to "aspects" throughout the specification mean that a particular element (e.g., a feature, structure, step, or characteristic) described in conjunction with that aspect is included in at least one aspect described herein, and may or may not be present in other aspects. In addition, it should be understood that the described elements may be combined in any suitable manner in the various aspects.
[0104] When an element such as a layer, film, region, or substrate is referred to as being "on" another element, it can be directly on the other element or intervening elements may also be present. In contrast, when an element is referred to as being "directly on" another element, there are no intervening elements present.
[0105] Unless stated to the contrary herein, all test standards are the most current standards in effect as of the filing date of this application or, if priority is claimed, the filing date of the earliest priority application in which the test standards appear.
[0106] Unless defined otherwise, technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this disclosure belongs.
[0107] Although the above disclosure has been described with reference to exemplary embodiments, it will be appreciated by those skilled in the art that various changes may be made and equivalents may be substituted for its elements without departing from its scope. In addition, many modifications may be made to adapt specific circumstances or materials to the teachings of the disclosure without departing from the basic scope of the disclosure. Therefore, it is intended that the disclosure is not limited to the specific embodiments disclosed, but will include all embodiments falling within its scope.
Claims
1. An electrode for an electrochemical cell, the electrode comprising: Electroactive materials; Conductive materials; as well as A binder comprising a lithiated maleic anhydride copolymer.
2. The electrode according to claim 1, comprising, based on the total weight of the electrode: 70 to 98 weight percent electroactive material; 1 to 20 wt % of a conductive material; and 1 to 20% by weight of a binder.
3. The electrode according to claim 1, wherein the lithiated maleic anhydride copolymer is formed by lithiation of a maleic anhydride copolymer represented by Formula I: wherein R is alkyl, ether, sulfate, amide, ester or nitrate.
4. The electrode of claim 1, wherein the lithiated maleic anhydride copolymer comprises poly(methyl vinyl ether-alt-lithium malate).
5. An electrochemical cell for cycling lithium ions, the electrochemical cell comprising: a first electrode comprising a first electroactive material, Conductive materials, and a binder comprising a lithiated maleic anhydride copolymer; a second electrode comprising a second electroactive material; and Electrolyte materials.
6. The electrochemical cell of claim 5, wherein the lithiated maleic anhydride copolymer is formed by lithiating a maleic anhydride copolymer represented by Formula I: wherein R is alkyl, ether, sulfate, amide, ester or nitrate.
7. The electrochemical cell of claim 5, wherein the electrolyte material comprises a lithium salt dissolved in an organic solvent.
8. The electrochemical cell of claim 7, wherein: The lithium salt includes lithium hexafluorophosphate, lithium perchlorate, lithium tetrachloroaluminate, lithium iodide, lithium bromide, lithium thiocyanate, lithium tetrafluoroborate, lithium difluorooxalatoborate, lithium tetraphenylborate, lithium bis(oxalate)borate, lithium tetrafluorooxalatophosphate, lithium nitrate, lithium hexafluoroarsenate, lithium trifluoromethanesulfonate, lithium bis(trifluoromethanesulfonyl imide), lithium fluorosulfonyl imide, lithium fluoroalkyl phosphate or a combination thereof; and The organic solvent includes cyclic carbonate, linear carbonate, aliphatic carboxylic acid ester, γ-lactone, chain structure ether, cyclic ether, sulfur compound or a combination thereof.
9. A method for forming an electrode binder, the method comprising: obtaining a maleic anhydride copolymer; as well as The maleic anhydride copolymer is lithiated to form the electrode binder.
10. The method according to claim 9, wherein the maleic anhydride copolymer is represented by Formula I: wherein R is alkyl, ether, sulfate, amide, ester or nitrate.